Socially Responsible Investment - Ballestero, Enrique (Springer, 2015)
This book integrates socially responsible investment into modern portfolio theory from a multi-criteria perspective. Socially responsible investment is a “new deal” championed by the institutional investment and bank sectors, agents that influence mutual funds and other collective investment schemes and which fear that financial strategies without ethical constraints can harm sustainable growth and prosperity. The book shows how to combine financial criteria such as profitability and risk with non-financial criteria such as the protection of the ecosystem, responsible consumption of energy, and healthcare campaigns. The book’s first part presents critical issues in ethical investment, while the second explains in detail the application of goal programming techniques for SRI funds, illustrating their use in actual cases. Part three demonstrates how compromise programming can be applied in the contexts of portfolio selection and risk management. Finally, in its fourth part the book examines the application of other decision-making support methods like the Analytic Hierarchy Process (AHP) framework, the Reference Point Method, and soft computing techniques for portfolio selection.